Critical Role of Pleural Wrap and Post-operative Neonatal Protocol in Long-gap Oesophageal Atresia: A Team Effort - Sanat Kumar Khanna; Vishal Vishnu Tiwari; Gurjot Singh; Gaurav Panchal (Wolters Kluwer Medknow Publications, 2024)
Background: The objectives of this study were to bring out the results of application of pleural wrap in primary repair of tracheo - esophageal fistula (TEF) with long-gap oesophageal atresia (LGEA) and also define the role of neonatologists and paediatric intensivists in post-operative management in these patients by laying down standard neonatal management protocol. Materials and Methods: This was a retrospective descriptive observational study conducted between March 2011 and April 2019 on 23 cases of LGEA with TEF. The study was conducted at two tertiary care paediatric surgery centres in Northern part of India wherein these newborn babies were operated by two paediatric surgeons with variable experience of 8-12 years. It also describes the neonatal management protocol used in post-operative period. Results: Out of 23 patients, 15 were boys and 8 were girls, with a mean age of 32.25 weeks and a mean birth weight of 2.02 kg. The mean hospital stay was 23.5 ± 8 days. Eleven cases had gap between 3 and 3.5 cm, 8 cases between 3.5 and 4 cm and 4 cases had gap more than 4 cm. The incidence of associated anomalies was 52%. Anastomotic leak rate was 8.69%, and 3 (13.04%) patients died in the post-operative period. All the operated patients were managed postoperatively as per strict neonatal management protocol exclusively by the team of neonatologists and neonatal intensivists. Conclusion: Application of pleural wrap over anastomosis following primary repair of LGEA with TEF significantly reduced the incidence of anastomotic leak in our study. Apart from the pleural wrap, the key to successful outcome also is contributed by the little prolonged, controlled ventilation and patience and perseverance in post-operative feeds. This post-operative management protocol that has been followed by us in our study is easily reproducible and can be adopted by paediatric surgeons working alongside neonatologists as a team.